Pembelajaran dengan pendekatan Contextual Teaching and Learning (CTL) dan problem posing ditinjau dari kemandirian belajar siswa SMPN 4 Banjarbaru - Asy'ari Asy'ari; Nonong Rahimah (Math Didactic: Jurnal Pendidikan Matematika, 2018)
The purpose of this study are to determine the effect of the learning models on the learning achievement in Mathematics viewed from the learning independence of the students. The learning models compared were the Contextual Teaching and Learning (CTL) model, the Problem Posing learning model, and the conventional learning model. The type of this study was a quasi-experimental study with a 3×3 factorial design. The study population was all grade VIII students of State Junior Secondary School 4 Banjarbaru. The samples in this study amounted to 87 students with the details of 29 students for experiment 1 and 28 students for experiments 2 and 30 students for the control class. The data collected instrument used mathematics achievement tests and a questionnaire of student’s learning independence. Based on the hypothesis, the results could be concluded as follows, the learning achievement of the students treated with CTL model was as good as that of those with the Problem Posing learning model. In addition, students’ learning achievement treated by CTL model and Problem Posing better than students treated by conventional learning model.